Pengaruh Viral Marketing dan Fear Of Missing Out terhadap Keputusan Pembelian Konsumen Produk Mixue di Kota Palembang - Hisbullah, M Arib Daffa; Purnamasari, Endah Dewi; Emilda, Emilda (Jurnal Nasional Manajemen Pemasaran dan SDM, 2023)
The purchasing decision is the result of the interaction between consumers' needs, motivations, perceptions, and attitudes towards products or services offered by marketers. Consumer purchasing decisions are influenced by their attitudes and subjective norms towards the products or services offered. This research aims to examine the influence of viral marketing and fear of missing out on purchasing decisions. The research is of a quantitative descriptive type, and data were collected through the distribution of questionnaires. A total of 100 respondents were successfully gathered by distributing questionnaires to Mixue product consumers in Palembang, Indonesia, using a combination of accidental sampling and homogeneous sampling techniques. The analysis technique used was a quantitative method based on the questionnaire distribution results. The analysis results show that, partially, viral marketing and fear of missing out each have a positive and significant impact on increasing purchasing decisions. Furthermore, simultaneously, viral marketing and fear of missing out variables together have a positive influence on increasing purchasing decisions.